(untitled) (Bioscience Journal, 2016)
The aim of this study was to evaluate the unilateral strength in knee flexion and extension, and the Hamstring/Quadriceps Ratio (H/Q Ratio), in dominant and non-dominant lower limbs in professional dancers. This was a cross-sectional study, carried out with 12 health adults (27.5±1.27years, 66.6±3.11kg, 173±0.02cm, 22.1±0.51kg/m2), professional dancers of a national company. The volunteers, after physical measurements, were submitted to a 1 Repetition Maximum (1RM) test, unilaterally, in both lower limbs at Flexor and Extensor Bench seat exercises. After 1 week, a 1RM retest was carried out to confirm the real total load for each limb. The torque and H/Q Ratio were calculated unilaterally. In knee extension, the dominant limb presented strength 18.77% higher than non-dominant limb (p<0.01), and in knee flexion, the strength of the dominant limb was 16.38% higher than the non-dominant limb (p=0.04). The H/Q Ratio was higher in the non-dominant limb 90.12 ± 0.22% than dominant limb 86.36±0.37% (p=0.04). The results showed difference in the strength between dominant and non-dominant members in both movements, knee flexion and extension. The H/Q Ratio presented values that evidenced imbalance in lower limbs. The population of dancers under study presented risk for injuries in lower limbs, requiring a specific training intervention.